ILRI and One Health - How we will prevent future pandemics - International Livestock Research Institute (International Livestock Research Institute, 2020)
What is One Health? ILRI Director General Jimmy Smith believes this approach is essential to prevent future pandemics like COVID-19. This is a recording of a session on One Health research at ILRI from a virtual town hall meeting on 24 April 2020. ILRI scientists Eric Fevre, Delia Randolph, Kristina Röesel, Bernard Bett and Hung Nguyen, and ILRI deputy directors Iain Wright and Dieter Schillinger are interviewed in the film. Read about this session: https://www.ilri.org/news/covid-19-de... Learn more about ILRI's work in One Health at http://ilri.org/zoonoses